(untitled) (American Journal of Islam and Society, 2010)
From 25 July to 6 August 2010, a select group of scholars invited by the International Institute of Islamic Thought (IIIT) analyzed “The Relationship between the Qur’an and the Sunnah.” Chaired by Mahmoud Ayoub (Hartford Seminary), this twenty-session event focused on how Muslims are dealing with Islam’s two core sources in the twenty-first century